2001
DOI: 10.1038/sj.bmt.1703014
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding hepatic veno-occlusive disease: what do we know and where are we going?

Abstract: Summary:Hepatic venocclusive disease (V0D) is a common toxicity associated with myeloablative chemotherapy or chemoradiotherapy used to prepare patients for stem cell transplantation. A sizable proportion of patients who develop VOD die. It is clear that injury to endothelial cells and hepatocytes in zone 3 of the liver acinus is the initial event in the pathogenesis of VOD. What are less clear are the mechanisms of injury and whether this knowledge can be exploited. This manuscript will briefly review some re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 67 publications
0
23
0
2
Order By: Relevance
“…3,10,11 The course of VOD ranges from a mild reversible one to a severe syndrome associated with multiorgan failure. [1][2][3][4] Treatment is usually supportive, as approximately half of the patients with uncomplicated VOD ultimately recover spontaneously. 12 The precise sequence of events leading to the development of VOD is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,10,11 The course of VOD ranges from a mild reversible one to a severe syndrome associated with multiorgan failure. [1][2][3][4] Treatment is usually supportive, as approximately half of the patients with uncomplicated VOD ultimately recover spontaneously. 12 The precise sequence of events leading to the development of VOD is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] VOD is an important regimen-related toxicity observed after hematopoietic stem cell transplant (HSCT). [1][2][3][4][5][6][7][8][9] VOD is usually diagnosed based on clinical findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 In addition, we have shown that busulfanthiotepa (BU TTP) is an effective salvage therapy for relapsed medulloblastoma in children. 8,9 Hepatic veno-occlusive disease (HVOD) 10,11 is the most severe and frequent extrahematological toxicity associated with high-dose busulfan in both adults and children. 12,13 Over the last 15 years, tremendous efforts have been expended to evaluate whether drug monitoring and dose adjustment could reduce the incidence and severity of busulfan-containing high-dose chemotherapy.…”
mentioning
confidence: 99%
“…El tratamiento de la EVOH propiamente tal es complejo y están en estudio marcadores que ayuden a un diagnóstico precoz, junto a un manejo de mayor eficacia antitrombótica con el uso de tPA, antitrombina III o defibrotide 18 . Se ha ensayado el manejo profiláctico con ácido ursodeoxicólico, heparina continua y de bajo peso molecular en los pacientes que requieren trasplante alogénico de médula ósea 19,20 . En nuestro paciente, el tratamiento anticoagulante estándar fue motivado precozmente por la trombosis portomesentérica e indujo una evolución favorable del compromiso postsinusoidal, probablemente en relación a la estasia con microtrombosis que se describió histológicamente a ese nivel, mostrando el hígado con volumen y flujo más normal, sin hipertensión portal al 5º mes.…”
Section: Discussionunclassified